Zöldségsnack-termék célpiacának felmérése - Marosi, Tibor; Makai, Andrea (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
Nowadays welfare societies give the possibility of choice for the wide selection and consumption of foods. The greatest parts of diseases typical of welfare are caused the wrong nutrition. Unfortunately this has been fortified by the contradictory messages of the media. The aim of this paper to form a picture about the healthy nutrition, as well as how the people are open for the new healthy food forms. Cooperating with a fresh food company we accomplished an assessment about the reception of a new vegetable snack product named Roppancs. The survey gives a possibility for the identification of potential consumer groups. Although the survey was not representative, some conclusion can be done. The 75% of the young people would by the product. The rate is the same for the benefit of females. The real price of the vegetable snack accepted by the people is the same as of popular chips. From the opinions it is stated that this product can be popular in the circles of conscious consumers.